Strategies of School Principals in Improving Educational Quality An Analysis of Best Practices in American Schools - Emily Jhonshon; Carlos Mendoza; Mochammad Syafiuddin Sobirin; Sutrisno (Pondok Pesantren As-salafiyah Asy-syafi'iyyah, 2024)
This research aims to examine the leadership practices of school principals in enhancing the quality of education within two private schools in the United States: Greenwood Academy and Sunshine Private School. Specifically, it seeks to identify effective leadership strategies that contribute to a positive learning environment and improved educational outcomes. Employing a qualitative case study approach, data were collected through semi-structured interviews with principals, teachers, and administrative staff, participatory observations, and document analysis. The study focused on exploring the roles of vision and mission, adaptive resource management, professional development for teachers, collaborative leadership, and data-driven decision-making in the context of educational leadership. The thematic analysis method was used to identify and interpret key themes from the collected data. The research findings indicate that effective school leadership significantly influences educational quality. The presence of a strong, inspiring vision serves as a motivational tool for both teachers and students. Furthermore, adaptive management of resources, particularly in budget-constrained environments, allows principals to creatively secure alternative funding. Support for professional development enhances teachers’ skills and motivation, leading to better student outcomes. Collaborative leadership fosters a harmonious work environment and encourages innovation, while data-driven decision-making equips principals with the necessary insights for effective problem-solving and program improvement. This study contributes to the understanding of effective educational leadership by showcasing innovative practices that enhance the overall quality of education in private schools.